Silicon-based negative electrode material and preparation method and application thereof

By using silicon-based anode material with modified gas-phase premagnesium in lithium-ion batteries, and using technical means such as tin and bismethylcyclopentadienyl magnesium, the problems of poor conductivity and insufficient cycling performance of silicon oxide materials are solved, and the problem of poor conductivity and insufficient cycling performance of silicon oxide materials is improved. The first-time Coulomb efficiency and cycle stability of the battery reduce cost and safety risks.

CN119153644AActive Publication Date: 2024-12-17HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411127132.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-17
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The poor conductivity, large expansion and poor circulation performance of silicon oxide materials in existing lithium-ion batteries have led to low efficiency and deterioration of circulation performance for the first time, and the use of lithium metal poses safety risks and high costs.

Method used

Using a silicon-based anode material with modified gas-phase premagnesium, the introduction of tin into the silicon oxide precursor in one-step method can reduce the diffusion energy barrier of lithium ions, and use bismethylcyclopentadienyl magnesium to vaporize premagnesium at low temperature. A uniform carbon cladding layer and a molybdenum disulfide-doped polyphenylene sulfide cladding layer are formed to improve the conductivity and structural stability of the material.

Benefits of technology

Improves the first-time Coulomb efficiency and cycle stability of the material, reduces expansion and cost, while enhancing the frequency of equipment and the high-temperature performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a silicon-based negative electrode material and a preparation method and application thereof. A main body material of the negative electrode material is a tin-doped pre-magnesium silicon oxide material, and the surface of the main body material is sequentially coated with a carbon layer and a molybdenum disulfide-doped polyphenylene sulfide coating layer; the preparation method comprises the following steps: S1, crushing silicon, silicon dioxide and tin, mixing, and tabletting; s2, sintering the tabletting material obtained in the step S1 to obtain a tin-doped silicon monoxide material; s3, crushing and grading the product in S2, and controlling the particle size distribution; s4, placing the product in S3 in a rotary kiln in an inert atmosphere, raising the temperature to a sintering temperature, placing dimethyl cyclopentadienyl magnesium in a gas reactor, sintering, and discharging at room temperature to obtain an intermediate product A; and S5, dispersing the product A and molybdenum disulfide in acetylacetone, adding diphenyl disulfide, introducing oxygen for reaction, and performing secondary heating reaction in a nitrogen atmosphere to obtain the molybdenum disulfide doped polyphenylene sulfide coated silicon-based negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] With the development of electric vehicles and portable electrical appliances, the demand for high energy density lithium-ion batteries is also increasing. The theoretical specific capacity of traditional graphite anode materials is only 372mAh / g, which is difficult to meet market demand. The first gram capacity of silicon materials is 4200mAh / g, with a higher lithium embedding platform, abundant crustal storage, and environmental friendliness, which has gradually attracted widespread attention from researchers.

[0003] However, the volume expansion of silicon is as high as 300%. During the cycle, it will not only cause the silicon to separate from the surrounding conductive carbon network to form "dead silicon", but also cause the silicon to peel off from the current collector. Secondly, the larger volume expansion will also cause the SEI film on the surface to be continuously reorganized and destroyed, making the SEI film thicker and thicker, constantly consuming the Li+ of the positive electrode, and reducing the coulombic efficiency. Finally, the larger volume expansion will cause the silicon material to pulverize in the later stage of the cycle. These problems ultimately lead to a sharp deterioration in the cycle performance.

[0004] Due to the above problems, academia and industry have shifted some of their attention to silicon oxide. Compared with nano-silicon, although silicon oxide sacrifices some capacity, its expansion is relatively small (~100%), and the byproducts such as lithium oxide, lithium silicate, and lithium metasilicate generated during the charge and discharge process can provide a buffering effect, greatly improving the cycle performance of the material. However, the conductivity of the material is relatively poor and the first efficiency is low. Lee DJ [Lee DJ, Ryou MH, Lee JN, et al. Nitrogen-doped carbon coating for a high-performance SiO anode in lithium-ion batteries[J]. Electrochemistry Communications, 2013, 34:98-101.] et al. prepared nitrogen-doped carbon-coated SiO material by liquid phase mixing + high-temperature carbonization. The material has relatively good cycle performance, but the first coulombic efficiency of the material is low. Jee HoYom et al. [Yom JH, Sun WH, Cho SM, et al. Improvement of irreversible behavior of SiO anodes for lithium ion batteries by a solidstate reaction at high temperature[J]. Journal of Power Sources, 2016, 311:159-166.] prepared high first-efficiency silicon-based negative electrode materials by solid-state reaction of SiO and lithium metal, followed by carbon coating. This method improved the first coulombic efficiency of the material, but the material's cycle performance was relatively poor. Since lithium metal was used as a reactant, the synthesis conditions were relatively harsh, there was a safety risk, and there was a risk of gas production during the battery slurry process. In addition, due to the generation of byproducts such as lithium silicate in the reaction, the electronic conductivity of the material was further reduced, and the cost was high. Of course, some patents such as CN201710193442.6 use magnesium vapor (high-temperature treatment of magnesium powder) to pre-magnesium silicon dioxide to improve its initial coulombic efficiency, but magnesium vapor will react with the heating system (molybdenum wire) to form molybdenum-magnesium alloy, causing damage to the heating system, affecting production efficiency and increasing costs. At the same time, the byproduct magnesium silicate phase generated by pre-magnesium hinders the diffusion of lithium ions during charging and discharging (the radius of magnesium ions is larger than that of lithium ions, and lithium ions need to bypass magnesium ions to diffuse), resulting in increased material impedance and affecting cycle and rate performance. CN201911024768.1 uses magnesium powder and magnesium oxide to pre-magnesium silicon dioxide solid phase, and the pre-magnesium uniformity is poor, and the silicon grains are relatively large, which affects circulation and expansion. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a modified gas phase pre-magnesium silicon-based negative electrode material and a preparation method thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A modified gas phase pre-magnesium silicon-based negative electrode material, wherein the main material is a tin-doped pre-magnesium silicon oxide material, and a carbon layer and a molybdenum disulfide-doped polyphenylene sulfide coating layer are sequentially coated on the surface of the main material; The method for preparing the modified gas phase pre-magnesium silicon-based negative electrode material comprises the following steps: S1, crushing silicon, silicon dioxide and tin, mixing them in a certain proportion and pressing them into tablets; S2, placing the tablet material obtained in S1 in a heating chamber of a kiln to control the vacuum degree for sintering, condensing and collecting in a collecting chamber, and discharging the material at room temperature after the reaction is completed to obtain a tin-doped silicon dioxide material; S3, crushing and classifying the tin-doped silicon oxide product of S2 to control the particle size distribution; S4, placing the product of S3 in a rotary kiln under the protection of an inert atmosphere and raising the temperature to a sintering temperature, placing dimethylcyclopentadienyl magnesium in a gas reactor of the rotary kiln, controlling the temperature of the gas reactor to gasify it, controlling the ratio of the mixed gas of the inert gas and dimethylcyclopentadienyl magnesium and the rotation speed of the rotary kiln, sintering, and discharging at room temperature to obtain an intermediate product A, i.e., a carbon-coated tin-doped pre-magnesium silicon oxide material; S5. Disperse the intermediate product A obtained in S4 and molybdenum disulfide in acetylacetone, then add diphenyl disulfide, and then introduce oxygen for reaction. After the reaction is completed, stop introducing oxygen, raise the temperature to 160-300°C under a nitrogen atmosphere, and keep warm for 0.5h-2h, then filter, wash, and dry to obtain a silicon-based negative electrode material doped with molybdenum disulfide and coated with polyphenylene sulfide.

[0007] Silicon oxide (SiO) has poor conductivity, low first efficiency and large expansion, which limits its wide application in the field of lithium-ion batteries. Pre-magnesium silicon oxide has large impedance, the grains are relatively difficult to control, and the cycle and rate performance are relatively poor. The present invention incorporates tin into the silicon lattice in a one-step process during the synthesis of silicon oxide precursors, triggers lattice expansion, reduces the diffusion energy barrier of lithium ions, and utilizes the equivalent isomorphism effect of tin and silicon atoms of the same family to improve the intrinsic ionic conductivity of the matrix material, thereby compensating for the negative impact of the increased impedance caused by subsequent magnesium incorporation. Due to the reduction of the lithium ion diffusion energy barrier, the proportion of lithium ions in the lattice that cannot be released due to being captured during lithium removal is greatly reduced, thereby playing a role in improving the first effect. Secondly, dimethylcyclopentadienyl magnesium with lower reaction activity (relative to magnesium powder and magnesium vapor) is used, through low-temperature vaporization, to form gas-solid contact uniform pre-magnesium with silicon oxide, forming magnesium ion pre-occupancy, thereby improving the first efficiency of the material. The reaction has low intensity and low heat generation, which is more conducive to controlling the size of silicon grains, thereby improving expansion and improving cycle performance. At the same time, the dimethylcyclopentadienyl groups present in the gas phase can also be uniformly carbonized to form a uniform and dense carbon coating layer, thereby improving the electrical conductivity of the material, and thus improving the cycle performance and rate performance. Dimethylcyclopentadienyl magnesium has low activity and is more friendly to equipment than magnesium, which can increase the frequency of use of the equipment and thus reduce costs. Finally, polyphenylene sulfide is in situ polymerized on the surface of the material and doped with molybdenum disulfide. The mechanical and electrical properties of doped polyphenylene sulfide are significantly improved, which can not only effectively buffer the volume expansion of the material, but also improve the structural stability. And polyphenylene sulfide itself has the characteristics of high temperature resistance and corrosion resistance, which can avoid the corrosion of HF to silicon oxide in the electrolyte, thereby improving the material cycle performance and high temperature performance.

[0008] Furthermore, the tin doping amount in the tin-doped pre-magnesium silicon oxide material is 2% to 5%, and tin is doped into the silicon lattice; the pre-magnesium amount is 8% to 16%, mainly present in the form of magnesium orthosilicate and magnesium metasilicate. The simple magnesium doping will react with the silicon dioxide in the silicon oxide to form magnesium silicate, forming a pre-occupied position, thereby improving the first effect of the material, but will cause the material impedance to increase. By utilizing the equivalent isomorphism effect of tin and silicon atoms of the same family (the tin atom has a larger radius, and the doping into the silicon lattice will cause the lattice to expand, thereby reducing the diffusion energy barrier of lithium ions), the intrinsic ionic conductivity of the matrix material can be improved, thereby compensating for the negative impact of the increased impedance caused by magnesium doping. Due to the reduction of the lithium ion diffusion energy barrier, the proportion of lithium ions in the lattice that cannot be removed due to being captured during lithium removal is greatly reduced, thereby playing a role in improving the first effect. Therefore, the co-doping of magnesium and tin can effectively improve the first effect through the synergistic effect of the two, while also compensating for the deficiency of magnesium doping, thereby improving the ionic conductivity. The mechanisms of improving the first efficiency of the two are different. Tin is doped into the silicon lattice inside silicon oxide, reducing the proportion of lithium ions that cannot escape from the silicon lattice during the charging and discharging process. Magnesium reacts with silicon dioxide inside silicon oxide to form a magnesium silicate phase, which forms a pre-occupied position in the material synthesis, thereby avoiding the lithium ions from the positive electrode consumed by side reactions during the charging process, thereby improving the first efficiency.

[0009] Furthermore, the mass of the carbon layer is 4% to 10% of the mass of the main material; the mass of the molybdenum disulfide-doped polyphenylene sulfide coating layer is 2% to 6% of the mass of the intermediate product A.

[0010] Furthermore, the mass ratio of molybdenum disulfide to polyphenylene sulfide in the molybdenum disulfide-doped polyphenylene sulfide coating layer is 1:1 to 1:4. If the ratio of molybdenum disulfide is too low, the conductivity of the polymer is poor, which affects the rate performance; if the ratio of molybdenum disulfide is too high, the mechanical strength of the polymer is poor, and the ability to inhibit the volume expansion of silicon becomes poor, so the ratio needs to be controlled.

[0011] Furthermore, in step S1, the median particle size D50 of silicon dioxide is 500nm~5000nm, the median particle size D50 of the tin particles is 10nm~500nm, the mass ratio of silicon, silicon dioxide and tin is 14:30:0.9~14:30:2.5 respectively; and the mixing method is kneading by adding water.

[0012] For subsequent uniform doping, this step S1 needs to control the particle size of the material. At the same time, the proportion distribution among the three is controlled. Too little tin will have little effect on the improvement of the material's first efficiency and ionic conductivity; too much tin doping will cause a "narrow channel" effect due to its large atomic radius, causing the diffusion channel to narrow, which in turn affects the diffusion and escape of lithium ions, but produces negative effects of increased impedance and reduced first efficiency, so the proportion of tin needs to be controlled.

[0013] Further, in step S2, the vacuum degree in S2 is 10Pa~100Pa, the temperature of the heating chamber is 1300℃~1800℃, and the temperature of the condensing chamber is 600℃~800℃. This step is mainly to generate tin-doped silicon oxide, and tin is uniformly doped into the silicon lattice inside the silicon oxide while synthesizing the silicon oxide precursor through a one-step gas phase reaction. Under vacuum conditions, not only the reaction energy barrier is reduced, but also the silicon oxide vapor and tin vapor generated by silicon and silicon dioxide are fully in contact, so as to achieve the purpose of fully uniform doping. In order to improve the quality of the product, it is necessary to control the temperature of the condensing chamber. If the temperature of the condensing chamber is too low, glassy silicon oxide will appear, affecting the circulation. If the temperature of the condensing chamber is too high, it will cause silicon oxide disproportionation and silicon grains to increase, which will not only lead to increased expansion, but also worsen the circulation. Therefore, it is necessary to control the temperature of the condensing chamber.

[0014] Further, in step S3, the graded particle size of tin-doped silicon oxide is Dmin≥1.5μm, D10≥3μm, 5≤D50≤7μm, Dmax≤10μm, and the value of (D90-D10) / D50 is controlled to be between 0.6 and 1. The purpose of controlling the SiO particle size distribution is to make the silicon oxide particle size distribution uniform, to prevent the problem of excessive pre-magnesium of small particles and insufficient pre-magnesium of large particles during subsequent pre-magnesium, which leads to deterioration of material properties. Therefore, the values ​​of Dmin and (D90-D10) / D50 are strictly controlled.

[0015] Furthermore, in step S4, the mass ratio of the S3 product to dimethylcyclopentadienyl magnesium is (0.72-1.59):1; the temperature of dimethylcyclopentadienyl magnesium in the gas reactor is 80°C~150°C; the inert gas is one or more of helium, neon, argon, krypton, and xenon; the volume ratio of the inert gas to dimethylcyclopentadienyl magnesium vapor is 4:1~1:1; the sintering process also needs to control the rotation speed of the rotary kiln, and the rotation speed of the rotary kiln is 0.25r / min~2r / min; the sintering is a two-stage sintering, the first stage sintering temperature is 300°C~500°C, the sintering time is 2h~6h, the second stage sintering temperature is 600°C~800°C, the sintering time is 2h~4h, and the heating rate of the sintering process is 1°C / min~3°C / min. Dimethylcyclopentadienyl magnesium has a low boiling point. It can be converted into steam with a slight heating to fully contact the dynamic silicon oxide material in the kiln. The gas-solid contact plus the dynamic rotation of the kiln make the pre-magnesium more uniform. At the same time, the activity of dimethylcyclopentadienyl magnesium is much lower than that of magnesium powder and magnesium vapor. Therefore, the silicon grains are easier to control, and the cycle performance is better while improving the first effect. Dimethylcyclopentadienyl magnesium is more equipment-friendly than magnesium, which can increase the frequency of equipment use. At the first sintering temperature, dimethylcyclopentadienyl magnesium vapor and silicon oxide react to uniformly pre-magnesium in the gas phase to obtain tin-doped pre-magnesium silicon oxide material. At the second sintering temperature, the dimethylcyclopentadienyl in the dimethylcyclopentadienyl is uniformly carbonized to form a uniform and dense carbon coating layer with good conductivity, thereby improving the cycle stability of the material. The two-stage temperature and heating rate need to be strictly controlled, mainly to reduce the grain size of silicon in silicon oxide while ensuring the conductivity of the carbon layer, thereby reducing expansion and improving cycle performance.

[0016] Furthermore, in step S5, the median particle size D50 of molybdenum disulfide is 10nm~200nm, the mass ratio of intermediate product A and molybdenum disulfide is 99:1~97:3, the mass ratio of intermediate product A and diphenyl disulfide is 99:1~96:4, the oxygen flow rate is 1ml / min~5ml / min, the reaction temperature is 20~60℃, and the reaction time is 0.5h~3h; the secondary heating temperature is 160~300℃, and the insulation time is 0.5h~2h.

[0017] This step S5 is mainly to form a conductive polymer coating layer of molybdenum disulfide doped polyphenylene sulfide on the surface of the material. At low temperature, acetylacetone is used to catalyze and control the oxygen flow rate to make diphenyl disulfide in situ oxidative polymerization on the surface of the material, and at the same time, the material will not be oxidized. Polyphenylene sulfide can be further melted, polycondensed, and further doped with molybdenum disulfide during the secondary temperature treatment to form a composite coating layer with good electronic and ionic conductivity coated on the surface of the silicon dioxide carbon layer. After being doped with molybdenum disulfide, the mechanical and electrical properties of polyphenylene sulfide are significantly improved, and it has its own high temperature resistance and corrosion resistance. It can not only effectively buffer the volume expansion of the material and improve the structural stability, but also avoid the corrosion of silicon dioxide by HF in the electrolyte, thereby improving the material cycle performance.

[0018] Another object of the present invention is to provide a modified gas-phase pre-magnesium silicon-based negative electrode material prepared by the above preparation method.

[0019] Another object of the present invention is to provide the use of the above-mentioned modified gas-phase pre-magnesium silicon-based negative electrode material in the preparation of lithium-ion batteries.

[0020] The invention also provides a lithium ion battery.

[0021] The lithium-ion battery comprises a positive electrode, a negative electrode, an electrolyte and a separator, and the material of the negative electrode comprises the silicon-based negative electrode material of the present invention.

[0022] The lithium-ion battery may include a button battery, a soft-pack battery, a hard-shell battery, and the like.

[0023] Taking button batteries as an example, the preparation method of the button batteries may include: mixing the modified gas-phase pre-magnesium silicon-based negative electrode material, conductive agent, and binder to obtain negative electrode slurry; coating the negative electrode slurry on the surface of the current collector, drying to obtain a negative electrode sheet, and then assembling the positive electrode sheet, negative electrode sheet, separator, electrolyte, and button battery shell in a glove box to obtain the button battery.

[0024] In the above-mentioned method for preparing a button cell, the positive electrode plate is generally a lithium plate. The separator may include one or a combination of two or more of Celgard 2400, Celgard 2325, Celgard 2500, etc. The electrolyte may include a lithium hexafluorophosphate solution. The button cell shell may include a CR2016 battery shell, a CR2023 battery shell, or a CR2450 battery shell.

[0025] The silicon-based material of the present invention is used as a negative electrode material to prepare a lithium-ion battery, and the electrochemical performance of the prepared lithium-ion battery is tested. The specific capacity, first efficiency and cycle stability of the prepared lithium-ion battery are all improved.

[0026] The first coulombic efficiency of traditional silicon oxide materials is low. The silicon oxide partially magnesiumized generates byproducts such as magnesium silicate, which not only further reduces the intrinsic electronic conductivity and ionic conductivity of the material, but also reacts too violently, causing the silicon grains to grow rapidly, further deteriorating the material's cycle performance and rate performance. At the same time, magnesium is not friendly to equipment and will reduce the service life of the equipment, thereby increasing material costs. The present invention aims to improve this defect.

[0027] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention dopes tin into the silicon lattice in one step during the synthesis of silicon oxide precursor, causing lattice expansion, reducing the diffusion energy barrier of lithium ions, and utilizing the equivalent isomorphism effect of tin and silicon atoms of the same family to improve the intrinsic ionic conductivity of the matrix material, thereby compensating for the negative impact of the increased impedance caused by the subsequent magnesium doping. Since the lithium ion diffusion energy barrier is reduced, the proportion of lithium ions that are trapped in the lattice and cannot be released during lithium removal is greatly reduced, thereby playing a role in improving the first effect.

[0028] 2) The present invention uses dimethylcyclopentadienyl magnesium with lower reactivity (relative to magnesium powder and magnesium vapor), which is vaporized at low temperature to form gas-solid contact with silicon oxide to uniformly pre-magnesium, forming magnesium ion pre-occupancy, thereby improving the initial efficiency of the material. The reaction intensity is low and the heat generation is small, which is more conducive to controlling the silicon grain size, thereby reducing expansion and improving cycle performance. At the same time, the dimethylcyclopentadienyl group present in the gas phase can also be uniformly carbonized to form a uniform and dense carbon coating layer, thereby improving the electrical conductivity of the material, thereby improving the cycle performance and rate performance.

[0029] 3) Dimethylcyclopentadienyl magnesium has low activity and is more equipment-friendly than magnesium. It can increase the frequency of equipment use and thus reduce costs.

[0030] 4) In-situ polymerization of polyphenylene sulfide on the surface of the material and doping with molybdenum disulfide are performed. The mechanical and electrical properties are significantly improved by doping with polyphenylene sulfide, which can not only effectively buffer the volume expansion of the material and improve the structural stability. In addition, polyphenylene sulfide itself has the characteristics of high temperature resistance and corrosion resistance, which can prevent HF in the electrolyte from corroding silicon oxide, thereby improving the material's cycle performance and high temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is an EDS mapping diagram of magnesium in the silicon-based negative electrode material prepared in Example 1; Figure 2 This is an EDS mapping diagram of magnesium in the silicon-based negative electrode material prepared in Comparative Example 1; Figure 3 The XRD diagrams of silicon-based negative electrode materials prepared in Example 1 and Comparative Example 4 and Comparative Example 1; Figure 4 The first charge and discharge curves of the silicon-based negative electrode material prepared in Example 1 and Comparative Example 1 at 0.1C; Figure 5 The graphs are rate performance diagrams of the materials mixed with graphite in Example 1, Comparative Example 1 and Comparative Example 2 under full battery conditions; Figure 6 The DCR curves of the materials mixed with graphite in Example 1, Comparative Example 1 and Comparative Example 2 under full battery conditions; Figure 7 The HPPC curves (power density diagram) of the materials mixed with graphite in Example 1 and Comparative Example 1 and Comparative Example 2 under full battery; Figure 8 The graphite-doped materials of Example 1 and Comparative Example 1 and Comparative Example 2 are shown in the full cell cycle performance curve at 1C / 1C current density. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0033] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0034] Example 1 2.8 kg of silicon, 6.6 kg of silicon dioxide (D50: 5000 nm), and 0.18 kg of tin (D50: 500 nm) were mixed with water, tableted, and dried.

[0035] The above materials are placed in a heating chamber of a kiln and the vacuum degree is controlled to be 10Pa. The temperature is raised to 1300°C for reaction. The temperature of the collecting chamber is controlled to be 600°C for condensation and collection. After the reaction is completed, the material is discharged at room temperature to obtain tin-doped silicon dioxide material.

[0036] The above materials were placed in a jet mill for crushing and classification, and Dmin was controlled to be 1.5 μm, D10 ≥ 3 μm, D50 to be 6 μm, Dmax to be 10 μm, and the value of (D90-D10) / D50 to be controlled to be 1.

[0037] 840 g of the crushed material was placed in a rotary kiln protected by an argon atmosphere, 1160 g of dimethylcyclopentadienyl magnesium (160 g in terms of magnesium) was placed in a gas reactor (container H) of the rotary kiln, the rotation speed of the rotary kiln was controlled to be 2 r / min, and the temperature was raised to 500° C. at 3° C. / min. At this time, the container H was heated to 80° C. to vaporize the dimethylcyclopentadienyl magnesium, and the gas ratio of argon and dimethylcyclopentadienyl magnesium vapor was controlled to be 4:1 (v / v) and enter the rotary kiln. The reaction time was 2 h at 500° C. to completely volatilize the dimethylcyclopentadienyl magnesium in the container H, and then the temperature was raised to 800° C. and kept for 4 h to completely carbonize the dimethylcyclopentadienyl group, and the intermediate product A was obtained by discharging at room temperature.

[0038] 97g of intermediate product A and 3g of molybdenum disulfide (D50: 200nm) were dispersed in acetylacetone, and then 2g of diphenyl disulfide was added, and oxygen was introduced at a flow rate of 1ml / min to react at 60°C for 3h, and the introduction of oxygen was stopped. The temperature was raised to 300°C under a nitrogen atmosphere and kept warm for 0.5h. Then, it was filtered, washed, and dried to obtain a molybdenum disulfide-doped polyphenylene sulfide-coated silicon negative electrode material, that is, a modified gas-phase pre-magnesium silicon-based negative electrode material.

[0039] The mass of the carbon layer of the material accounts for 10% of the mass of the main material (tin-doped pre-magnesium silicon oxide material), and the molybdenum disulfide-doped polyphenylene sulfide coating layer accounts for 5% of the mass of the intermediate product A (carbon-coated tin-doped pre-magnesium silicon oxide material).

[0040] Figure 1 The EDS image of the magnesium element in the silicon-based negative electrode material prepared in Example 1 shows that the magnesium element is distributed relatively evenly within the material. Figure 2 The EDS diagram of magnesium element in comparative example 1 shows that magnesium element is unevenly distributed, and part of it is distributed in a gradient. This is because Example 1 uses bismethylcyclopentadienyl magnesium vapor phase dynamic pre-treatment, so magnesium distribution is relatively uniform.

[0041] Figure 3 The XRD diagrams of Example 1, Comparative Example 1 and Comparative Example 4 show that both magnesium orthosilicate phase and metasilicic acid phase appear in the materials, which is due to pre-magnesium. However, the material prepared in Example 1 has the largest half-peak width of crystalline silicon diffraction at about 28.4°C, followed by Comparative Example 1, and the smallest is the material prepared in Comparative Example 4. This reflects that the material prepared in Example 1 has the smallest silicon grains, which is beneficial to reducing expansion and improving the material cycle performance. This phenomenon occurs because Example 1 uses less active dimethylcyclopentadienyl magnesium vapor (relative to magnesium powder) for gas phase dynamic pre-magnesium, so the reaction is more controllable and uniform, and the heat generation is small, so the grains are the smallest and the cycle performance is the best.

[0042] The prepared silicon-based negative electrode material: SP: LA133 = 8:1:1 ratio (mass ratio) was mixed and coated on 8μm copper foil to prepare the negative electrode sheet. The lithium sheet was used as the counter electrode to assemble the CR2016 button battery. The electrolyte used was 1mol / L LiPF 6 EC+DMC (1:1, v / v) solution was prepared and the electrochemical performance was tested.

[0043] The results are as follows Figure 4 As shown in Table 1, at a current density of 0.1C, the material prepared in Example 1 has a first discharge capacity of 1561.4 mAh / g, a charge capacity of 1380.3 mAh / g, and a first coulombic efficiency of 88.4%. After 50 cycles, the capacity is 1298.9 mAh / g, and the capacity retention rate is 94.1%. At the same time, the silicon grain size of the material prepared in Example 1 is 5.5 nm, the powder resistance is 0.81 Ω / cm, and the lithium ion diffusion coefficient is 8.2×10 -8 m 2 / s.

[0044]

[0045] Comparative Example 1 Commercial pre-magnesium silicon oxide materials are used, and the synthesis method mainly uses magnesium powder as the magnesium source and uses a CVD process for carbon coating; Comparative Example 2 The difference from Example 1 is that: in Example 1, no tin is added; Comparative Example 3 The difference from Example 1 is that: Example 1 does not add tin, does not use bismethylcyclopentadienyl magnesium, and the carbon coating is CVD coating; Comparative Example 4 The difference from Example 1 is that: in Example 1, bismethylcyclopentadienyl magnesium is not used, and magnesium powder and acetylene are used for CVD carbon coating; Comparative Example 5 The difference from Example 1 is that: in Example 1, polyphenylene sulfide coating is not used; Comparative Example 6 The difference from Example 1 is that molybdenum disulfide is not used in Example 1.

[0046] The materials prepared in Comparative Examples 1 to 6 were mixed and coated in a ratio of SP:LA133=8:1:1 (mass ratio) to assemble CR2016 button batteries. The electrolyte used was 1 mol / L LiPF 6EC+DMC solution was used to test the electrochemical performance. The results are shown in Table 1. At a current density of 0.1C, the material prepared in Comparative Example 1 has a first discharge capacity of 1531.8mAh / g, a charge capacity of 1299mAh / g, and a first coulombic efficiency of 84.8%. After 50 cycles, the specific capacity is 1131.4mAh / g, and the capacity retention rate is 87.1%. The silicon grains of the material prepared in Comparative Example 1 are 7.2nm, the powder resistance is 1.13Ω / cm, and the lithium ion diffusion coefficient is 2×10 -10 m 2 / s. Figure 4 It can be found that in the charge and discharge curve diagram of Example 1, the lithium insertion platform on its discharge curve is higher, and the discharge curve is more inclined, and there is no obvious lithium desorption characteristic platform at 0.4V. This is due to the smaller grains of the material prepared in Example 1. By comparing Example 1 with Comparative Example 1, it can be found that the material prepared by the present invention is superior to the commercial material in discharge specific capacity, first efficiency, and cycle capacity retention rate. At the same time, the silicon grains of the prepared material are smaller and have a higher lithium ion diffusion coefficient. This is because Example 1 uses less active dimethylcyclopentadienyl magnesium vapor (relative to magnesium powder) for gas phase dynamic pre-magnesium, so the reaction is more controllable and uniform, and the heat generation is small, so the grains are smallest and the cycle performance is optimal. At the same time, polyphenylene sulfide doped with molybdenum disulfide is used for modification, and its mechanical properties and electrical properties are significantly improved, which can effectively buffer the volume expansion of the material and improve the structural stability. In addition, in Example 1, tin doping is performed during the precursor synthesis to induce lattice expansion in advance, reduce the diffusion energy barrier of lithium ions, and utilize the equivalent isomorphism effect of tin and silicon atoms of the same family to improve the ionic conductivity of the matrix material, thereby compensating for the negative impact of the increased impedance caused by the subsequent magnesium doping, thereby improving the rate performance.

[0047] The material prepared in comparative example 2 has a first discharge capacity of 1539 mAh / g, a charge capacity of 1311.2 mAh / g, and a first coulombic efficiency of 85.2%. After 50 cycles, the capacity is 1111.2 mAh / g, and the capacity retention rate is 89.3%. At the same time, the silicon grain size of the material prepared in example 1 is 6.1 nm, the powder resistance is 0.96 Ω / cm, and the lithium ion diffusion coefficient is 4×10 - 10 m 2 / s. By comparing Example 1 with Comparative Example 2, it can be found that lattice doping of tin elements in silicon oxide particles in precursor synthesis can reduce the diffusion energy barrier (equivalent isomorphism effect), effectively improve the lithium ion diffusion coefficient, and thus improve the rate performance of the material ( Figure 5). As the lithium ion diffusion barrier is reduced, the proportion of lithium ions that are trapped in the lattice and cannot be released during lithium removal is greatly reduced, thereby improving the first efficiency. Therefore, compared with the simple use of magnesium reduction, tin doping and magnesium reduction can work synergistically to further improve the first coulombic efficiency of the material.

[0048] The material prepared in comparative example 3 has a first discharge capacity of 2060mAh / g, a charge capacity of 1610.9mAh / g, and a first coulombic efficiency of 78.2%. After 50 cycles, the capacity is 1490.1mAh / g, and the capacity retention rate is 89.3%. At the same time, the silicon grain size of the material prepared in comparative example 3 is 2.4nm, the powder resistance is 0.92Ω / cm, and the lithium ion diffusion coefficient is 1.2×10 -10 m 2 / s. By comparing Example 1 with Comparative Example 3, it can be found that since Comparative Example 3 does not undergo pre-magnesium treatment, the first efficiency of Comparative Example 3 is low, the grains are smaller (pre-magnesium treatment is an exothermic reaction, which will cause the grains to grow), and the cycle is relatively poor. This is mainly because the elastic modulus of the magnesium silicate phase formed by pre-magnesium treatment is higher, and the expansion capacity of the buffer material is stronger, so the structure is stable and the cycle is better.

[0049] The material prepared in Comparative Example 4 has a first discharge capacity of 1476.8 mAh / g, a charge capacity of 1302.5 mAh / g, and a first coulombic efficiency of 88.2%. After 50 cycles, the capacity is 1061.5 mAh / g, and the capacity retention rate is 81.5%. At the same time, the silicon grain size of the material prepared in Comparative Example 4 is 7.8 nm, the powder resistance is 1.25 Ω / cm, and the lithium ion diffusion coefficient is 6.5×10 -8 m 2 / s. By comparing Example 1 with Comparative Example 4, it can be found that the silicon grains in Example 1 are smaller and the cycle is better. This is because Comparative Example 4 uses magnesium powder to replace dimethylcyclopentadienyl magnesium and performs CVD coating. Since the reaction activity of magnesium powder is higher than that of dimethylcyclopentadienyl magnesium, and magnesium powder and the material are in solid-solid contact, while dimethylcyclopentadienyl magnesium is gasified at low temperature and the material is in gas-solid contact, the latter has better reaction uniformity, low reaction activity, and stronger reaction controllability. Therefore, Example 1 has smaller grains and better cycle.

[0050] The material prepared in comparative example 5 has a first discharge capacity of 1509.2 mAh / g, a charge capacity of 1332.2 mAh / g, and a first coulombic efficiency of 88.3%. After 50 cycles, the capacity is 1202 mAh / g, and the capacity retention rate is 90.2%. At the same time, the silicon grain size of the material prepared in example 1 is 5.6 nm, the powder resistance is 0.64 Ω / cm, and the lithium ion diffusion coefficient is 7.8×10 - 8 m 2 / s. By comparing Example 1 with Comparative Example 5, it can be found that Comparative Example 5 only uses molybdenum disulfide coating. Although the impedance of the material is reduced, the cycle performance of the material is reduced. This is because Comparative Example 5 does not use polyphenylene sulfide coating, and the mechanical strength of its coating layer is not enough to improve the huge volume expansion of silicon during the charge and discharge process.

[0051] The material prepared in Comparative Example 6 has a first discharge capacity of 1491.2 mAh / g, a charge capacity of 1309.3 mAh / g, and a first coulombic efficiency of 87.8%. After 50 cycles, the capacity is 1195.4 mAh / g, and the capacity retention rate is 91.3%. At the same time, the silicon grain size of the material prepared in Example 1 is 5.5 nm, the powder resistance is 3.45 Ω / cm, and the lithium ion diffusion coefficient is 5.4×10 -8 m 2 By comparing Example 1 with Comparative Example 6, it can be found that Comparative Example 6 is only coated with polyphenylene sulfide, and its conductivity is poor, resulting in a sharp increase in the powder resistivity of the material, while also affecting the ionic conductivity of the material, thereby affecting the material's cycle performance and rate performance.

[0052] Based on the above, the performance of the material prepared in Example 1 is better through the above steps and the raw materials and proportions used.

[0053] With NCM622 as the positive electrode, the materials prepared in Example 1 and Comparative Example 1 vs. 2 were mixed with artificial graphite to 420 mAh / g and used as the negative electrode, and 10Ah soft-pack batteries were assembled through the processes of slurry mixing, coating, rolling, slitting, die cutting, lamination, welding of pole ears, top and side sealing, baking, and liquid injection. After the batteries were divided into different capacities, short-term performance tests were carried out. The results are as follows: Figures 5 to 7 As shown, the current full battery cycle is 1200 weeks, and the capacity retention rate is 86.5%. The material after blending in Comparative Example 1 has the smallest DCR (50% DOD: 21.45mΩ), the largest constant current charging ratio (3C: 63.4%), and the largest power density in the HPPC test (50% DOD: 2196.44W / kg). The rate performance and power performance of the material are better. This is because Example 1 uses tin doping, and utilizes the isovalent and isostructural effect of tin and silicon to reduce the lithium ion diffusion energy barrier and improve the ionic conductivity of the material. Regardless of whether it is the commercial Comparative Example 1 material or Comparative Example 2 that only uses pre-magnesium, the magnesium ion radius in the magnesium silicate phase formed by the pre-occupancy is large, which hinders the diffusion of lithium ions into the interior during the lithium insertion process, resulting in increased impedance, thereby affecting the rate and power performance. Subsequently, a room temperature cycle test at 25°C was carried out at a current density of 1C / 1C. The results are as follows Figure 8As shown, after 600 cycles of Example 1, the capacity retention rate is 93.4%, while the capacity retention rates of Comparative Example 1 and Comparative Example 2 after 500 cycles are 90.5% and 86.4%, respectively. The cycle performance of Example 1 is significantly improved. This is because Example 1 not only uses tin doping, but also uses the isovalent and isostructural effect of tin and silicon to improve the lithium ion conductivity of the material. It also uses dimethylcyclopentadienyl magnesium vapor (relative to magnesium powder and magnesium vapor) with lower reaction activity, low reaction intensity, low heat generation, and is more conducive to controlling the silicon grain size, thereby reducing expansion and improving cycle performance. At the same time, the dimethylcyclopentadienyl groups present in the gas phase can also be uniformly carbonized to form a uniform and dense carbon coating layer, improve the conductivity of the material, and then improve the cycle performance and rate performance. Finally, polyphenylene sulfide is also in-situ polymerized on the surface of the material and doped with molybdenum disulfide. The mechanical and electrical properties of polyphenylene sulfide are significantly improved by doping, which can not only effectively buffer the volume expansion of the material, but also improve the structural stability. Moreover, polyphenylene sulfide itself has the characteristics of high temperature resistance and corrosion resistance, which can prevent HF in the electrolyte from corroding silicon oxide, thereby improving the material's cycle performance and high temperature performance.

[0054] Example 2 2.8 kg of silicon, 6.6 kg of silicon dioxide (D50: 500 nm), and 0.46 kg of tin (D50: 10 nm) were mixed with water, pressed into tablets, and dried.

[0055] The above materials are placed in a heating chamber of a kiln and the vacuum degree is controlled to be 100Pa. The temperature is raised to 1800°C for reaction. The temperature of the collecting chamber is controlled to be 600°C for condensation and collection. After the reaction is completed, the material is discharged at room temperature to obtain tin-doped silicon dioxide material.

[0056] The above materials were placed in a jet mill for pulverization and classification, and Dmin, D10, D50, Dmax, and (D90-D10) / D50 were controlled to be 2 μm, 3.5 μm, 6 μm, and 9 μm, respectively, and the value of (D90-D10) / D50 was controlled to be 0.8.

[0057] 920 g of the crushed material was placed in a rotary kiln protected by an argon atmosphere, 580 g of dimethylcyclopentadienyl magnesium (80 g in terms of magnesium) was placed in a gas reactor (container H) of the rotary kiln, the rotation speed of the rotary kiln was controlled to be 0.25 r / min, and the temperature was increased to 300° C. at 1° C. / min. At this time, the container H was heated to 150° C. to vaporize the dimethylcyclopentadienyl magnesium, and the gas ratio of argon and dimethylcyclopentadienyl magnesium vapor was controlled to be 1:1 and enter the rotary kiln. The reaction time was 6 hours at 300° C. to completely volatilize the dimethylcyclopentadienyl magnesium in the container A, and then the temperature was increased to 800° C. and kept for 4 hours to completely carbonize the dimethylcyclopentadienyl group, and the intermediate product A was obtained by discharging at room temperature.

[0058] 99g of intermediate product A and 1g of molybdenum disulfide (D50: 10nm) were dispersed in acetylacetone, and then 1g of diphenyl disulfide was added, and oxygen was introduced at a flow rate of 5ml / min to react at 20°C for 3h, and the introduction of oxygen was stopped. The temperature was raised to 160°C under a nitrogen atmosphere and kept for 2h, and then filtered, washed, and dried to obtain a molybdenum disulfide-doped polyphenylene sulfide-coated silicon negative electrode material, that is, a modified gas-phase pre-magnesium silicon-based negative electrode material.

[0059] The mass of the carbon layer of the material accounts for 4% of the mass of the main material, and the molybdenum disulfide-doped polyphenylene sulfide coating layer accounts for 2% of the mass of the intermediate product A.

[0060] The prepared silicon-based negative electrode material: SP: LA133 = 8:1:1 ratio was mixed and coated, and CR2016 button batteries were assembled. The electrolyte used was 1 mol / L LiPF 6 EC+DMC solution was prepared and the electrochemical performance was tested. The electrochemical test was also carried out according to the above steps. The test results are shown in Table 2. The material prepared in Example 2 has a first discharge capacity of 1823.2mAh / g, a charge capacity of 1462.2mAh / g, and a first coulombic efficiency of 80.2%. After 50 cycles, the specific capacity was 1430mAh / g, and the capacity retention rate was 97.8%. At the same time, the silicon grains of the material prepared in Example 2 were 3.1nm, the powder resistance was 0.64 Ω / cm, and the lithium ion diffusion coefficient was 8.6×10 -8 m 2 / s.

[0061] Example 3 2.8 kg of silicon, 6.6 kg of silicon dioxide (D50: 2000 nm), and 0.27 kg of tin (D50: 100 nm) were mixed with water, tableted, and dried.

[0062] The above materials are placed in a heating chamber of a kiln and the vacuum degree is controlled to be 10Pa. The temperature is raised to 1500°C for reaction. The temperature of the collecting chamber is controlled to be 700°C for condensation and collection. After the reaction is completed, the material is discharged at room temperature to obtain tin-doped silicon dioxide material.

[0063] The above materials were placed in a jet mill for pulverization and classification, and Dmin, D10, D50, Dmax, and (D90-D10) / D50 were controlled to be 2 μm, 3.2 μm, 3.2 μm, 5 μm, and 9 μm, respectively. The value of (D90-D10) / D50 was controlled to be 1.

[0064] 900 g of the crushed material was placed in a rotary kiln protected by an argon atmosphere, 725 g of dimethylcyclopentadienyl magnesium (100 g in terms of magnesium) was placed in a gas reactor (container H) of the rotary kiln, the rotation speed of the rotary kiln was controlled to be 1 r / min, and the temperature was raised to 400°C at 2°C / min. At this time, the container H was heated to 100°C to vaporize the dimethylcyclopentadienyl magnesium, and the gas ratio of argon and dimethylcyclopentadienyl magnesium vapor was controlled to be 2:1 and entered the rotary kiln. The reaction time was 3 hours at 400°C to completely volatilize the dimethylcyclopentadienyl magnesium in the container H, and then the temperature was raised to 700°C and kept for 3 hours to completely carbonize the dimethylcyclopentadienyl group, and the intermediate product A was obtained by discharging at room temperature.

[0065] 98g of intermediate product A and 2g of molybdenum disulfide (D50: 50nm) were dispersed in acetylacetone, and then 2g of diphenyl disulfide was added, and oxygen was introduced at a flow rate of 2ml / min to react at 40°C for 1h. The introduction of oxygen was stopped, and the temperature was raised to 200°C under a nitrogen atmosphere and kept for 1h. Then, it was filtered, washed, and dried to obtain a molybdenum disulfide-doped polyphenylene sulfide-coated silicon negative electrode material, that is, a modified gas-phase pre-magnesium silicon-based negative electrode material.

[0066] The mass of the carbon layer of the material accounts for 6% of the mass of the main material, and the molybdenum disulfide-doped polyphenylene sulfide coating layer accounts for 4% of the mass of the intermediate product A.

[0067] The prepared silicon-based negative electrode material: SP: LA133 = 8:1:1 ratio was mixed and coated, and CR2016 button batteries were assembled. The electrolyte used was 1 mol / L LiPF6 EC+DMC solution, and the electrochemical performance test was performed. The electrochemical test was also carried out according to the above steps. The test results are shown in Table 2. The material prepared in Example 3 had a first discharge capacity of 1749.3 mAh / g, a charge capacity of 1432.7 mAh / g, and a first coulombic efficiency of 81.9%. After 50 cycles, the capacity was 1384 mAh / g, and the capacity retention rate was 96.6%. At the same time, the silicon grains of the material prepared in Example 3 were 3.8 nm, the powder resistance was 0.93 Ω / cm, and the lithium ion diffusion coefficient was 9.5×10 -8 m 2 / s.

[0068] Example 4 2.8 kg of silicon, 6.6 kg of silicon dioxide (D50: 1000 nm), and 0.367 kg of tin (D50: 200 nm) were mixed with water, pressed into tablets, and dried.

[0069] The above materials are placed in a heating chamber of a kiln and the vacuum degree is controlled to be 50Pa. The temperature is raised to 1600°C for reaction. The temperature of the collecting chamber is controlled to be 650°C for condensation and collection. After the reaction is completed, the material is discharged at room temperature to obtain tin-doped silicon dioxide material.

[0070] The above materials were placed in a jet mill for pulverization and classification, and Dmin was controlled to be 3 μm, D10≥4.2 μm, D50 to be 7 μm, Dmax to be 9.5 μm, and the value of (D90-D10) / D50 to be controlled to be 0.7.

[0071] 880 g of the crushed material was placed in a rotary kiln protected by an argon atmosphere, 870 g of dimethylcyclopentadienyl magnesium (120 g in terms of magnesium) was placed in a gas reactor (container H) of the rotary kiln, the rotation speed of the rotary kiln was controlled to be 0.5 r / min, and the temperature was raised to 450° C. at 3° C. / min. At this time, the container H was heated to 120° C. to vaporize the dimethylcyclopentadienyl magnesium, and the gas ratio of argon and dimethylcyclopentadienyl magnesium vapor was controlled to be 3:1 and entered the rotary kiln. The reaction time was 4 hours at 450° C. to completely volatilize the dimethylcyclopentadienyl magnesium in the container H, and then the temperature was raised to 800° C. and kept for 2 hours to completely carbonize the dimethylcyclopentadienyl group, and the intermediate product A was obtained by discharging at room temperature.

[0072] 96g of intermediate product A and 1g of molybdenum disulfide (D50: 30nm) were dispersed in acetylacetone, and then 3g of diphenyl disulfide was added, and oxygen was introduced at a flow rate of 2ml / min to react at 60°C for 0.5h, and the introduction of oxygen was stopped. The temperature was raised to 250°C under a nitrogen atmosphere and kept for 1h. Then, it was filtered, washed, and dried to obtain a molybdenum disulfide-doped polyphenylene sulfide-coated silicon negative electrode material, that is, a modified gas-phase pre-magnesium silicon-based negative electrode material.

[0073] The mass of the carbon layer of the material accounts for 7% of the mass of the main material, and the molybdenum disulfide-doped polyphenylene sulfide coating layer accounts for 4% of the mass of the intermediate product A.

[0074] The prepared silicon-based negative electrode material: SP: LA133 = 8:1:1 ratio was mixed and coated, and CR2016 button batteries were assembled. The electrolyte used was 1 mol / L LiPF 6 EC+DMC solution was prepared and the electrochemical performance was tested. The electrochemical test was also carried out according to the above steps. The test results are shown in Table 2. The material prepared in Example 4 has a first discharge capacity of 1655.3 mAh / g, a charge capacity of 1392.1 mAh / g, and a first coulombic efficiency of 84.1%. After 50 cycles, the capacity was 1335 mAh / g, and the capacity retention rate was 95.9%. At the same time, the silicon grains of the material prepared in Example 4 were 4.6 nm, the powder resistance was 0.72 Ω / cm, and the lithium ion diffusion coefficient was 1.6×10-7 m 2 / s.

[0075] Example 5 2.8 kg of silicon, 6.6 kg of silicon dioxide (D50: 800 nm), and 0.4 kg of tin (D50: 120 nm) were mixed with water, pressed into tablets, and dried.

[0076] The above materials are placed in a heating chamber of a kiln and the vacuum degree is controlled to be 10Pa. The temperature is raised to 1400°C for reaction. The temperature of the collecting chamber is controlled to be 650°C for condensation and collection. After the reaction is completed, the material is discharged at room temperature to obtain tin-doped silicon dioxide material.

[0077] The above materials were placed in a jet mill for pulverization and classification, and Dmin, D10, D50, Dmax, and (D90-D10) / D50 were controlled to be 2.6 μm, 4.3 μm, 7 μm, and 9.3 μm, respectively. The value of (D90-D10) / D50 was controlled to be 0.6.

[0078] 860 g of the crushed material was placed in a rotary kiln protected by an argon atmosphere, 1015 g of dimethylcyclopentadienyl magnesium (140 g in terms of magnesium) was placed in a gas reactor (container H) of the rotary kiln, the rotation speed of the rotary kiln was controlled to be 2 r / min, and the temperature was raised to 350° C. at 3° C. / min. At this time, the container H was heated to 90° C. to vaporize the dimethylcyclopentadienyl magnesium, and the gas ratio of argon and dimethylcyclopentadienyl magnesium vapor was controlled to be 3:1 and entered the rotary kiln. The reaction time was 6 hours at 350° C. to completely volatilize the dimethylcyclopentadienyl magnesium in the container H, and then the temperature was raised to 800° C. and kept for 4 hours to completely carbonize the dimethylcyclopentadienyl group, and the intermediate product A was obtained by discharging at room temperature.

[0079] 97g of intermediate product A and 3g of molybdenum disulfide (D50: 150nm) were dispersed in acetylacetone, and then 3g of diphenyl disulfide was added, and oxygen was introduced at a flow rate of 3ml / min to react at 60°C for 1h. The introduction of oxygen was stopped, and the temperature was raised to 300°C under a nitrogen atmosphere and kept for 6h. Then, it was filtered, washed, and dried to obtain a molybdenum disulfide-doped polyphenylene sulfide-coated silicon negative electrode material, that is, a modified gas-phase pre-magnesium silicon-based negative electrode material.

[0080] The mass of the carbon layer of the material accounts for 8% of the mass of the main material, and the molybdenum disulfide-doped polyphenylene sulfide coating layer accounts for 6% of the mass of the intermediate product A.

[0081] The prepared silicon-based negative electrode material: SP: LA133 = 8:1:1 ratio was mixed and coated, and CR2016 button batteries were assembled. The electrolyte used was 1 mol / L LiPF6 EC+DMC solution, and the electrochemical performance test was performed. The electrochemical test was also carried out according to the above steps. The test results are shown in Table 2. The material prepared in Example 5 had a first discharge capacity of 1608.5 mAh / g, a charge capacity of 1378.5 mAh / g, and a first coulombic efficiency of 85.7%. After 50 cycles, the capacity was 1312.3 mAh / g, and the capacity retention rate was 95.2%. At the same time, the silicon grains of the material prepared in Example 5 were 5.1 nm, the powder resistance was 0.75 Ω / cm, and the lithium ion diffusion coefficient was 1.2×10 -7 m 2 / s.

[0082] By comparing Example 1 to Example 5, it can be found that with the increase of the amount of pre-magnesium, the first effect of the material is improved, but the grains gradually increase, and the cycle performance is decreasing. This is because the magnesium content increases during the pre-magnesium process, and the heat release increases sharply, resulting in excessive grain growth, which in turn affects the cycle performance. At the same time, as the amount of tin doping in the precursor increases, the lithium ion diffusion coefficient tends to increase first and then decrease. This is because too much tin doping, due to its large atomic radius, will appear a "narrow channel" effect, resulting in the narrowing of the diffusion channel, which in turn affects the diffusion and escape of lithium ions, but increases the negative effects of increased impedance and reduced first effect. In summary, the proportion of tin doping and the amount of pre-magnesium need to be strictly controlled during the material preparation process.

[0083]

[0084] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.

Claims

1. A method for preparing a silicon-based negative electrode material, characterized in that: The main material of the silicon-based negative electrode material is a tin-doped pre-magnesium silicon oxide material, and a carbon layer and a molybdenum disulfide-doped polyphenylene sulfide coating layer are sequentially coated on the surface of the main material; The method for preparing the silicon-based negative electrode material comprises the following steps: S1, crushing silicon, silicon dioxide and tin, mixing them in a certain proportion and pressing them into tablets; S2, placing the tablet material obtained in S1 in a heating chamber of a kiln to control the vacuum degree for sintering, condensing and collecting in a collecting chamber, and discharging the material at room temperature after the reaction is completed to obtain a tin-doped silicon dioxide material; S3, crushing and classifying the tin-doped silicon oxide material to control the particle size distribution; S4, placing the product of S3 in a rotary kiln under the protection of an inert atmosphere and heating it to a sintering temperature, placing dimethylcyclopentadienyl magnesium in a gas reactor of the rotary kiln to gasify it, controlling the ratio of the mixed gas of the inert gas and dimethylcyclopentadienyl magnesium, sintering, and discharging at room temperature to obtain an intermediate product A, i.e., a carbon-coated tin-doped pre-magnesium silicon oxide material; S5. Disperse the intermediate product A obtained in S4 and molybdenum disulfide in acetylacetone, then add diphenyl disulfide, and then introduce oxygen to react. After the reaction is completed, stop introducing oxygen, and heat the reaction a second time under a nitrogen atmosphere. After the reaction is completed, filter, wash, and dry to obtain a molybdenum disulfide-doped polyphenylene sulfide-coated silicon-based negative electrode material.

2. The preparation method according to claim 1, characterized in that: The tin doping amount in the tin-doped pre-magnesium silicon oxide material is 2% to 5%, and the tin is doped into the silicon lattice; the pre-magnesium amount is 8% to 16%; And / or, the mass of the carbon layer is 4% to 10% of the mass of the tin-doped pre-magnesium silicon oxide material; the molybdenum disulfide-doped polyphenylene sulfide coating layer is 2% to 6% of the mass of the intermediate product A; And / or, the mass ratio of molybdenum disulfide to polyphenylene sulfide in the molybdenum disulfide-doped polyphenylene sulfide coating layer is 1:1 to 1:

4.

3. The preparation method according to claim 1 or 2, characterized in that: In the step S1, the median particle size D50 of the silicon dioxide is 500nm~5000nm, and the median particle size D50 of the tin particles is 10nm~500nm; And / or, the mass ratio of silicon, silicon dioxide and tin is 14:30:0.9 to 14:30:2.5; And / or, the mixing method is kneading by adding water.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S2, the vacuum degree is 10Pa~100Pa, the temperature of the heating chamber is 1300℃~1800℃, and the temperature of the condensing chamber is 600℃~800℃.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S3, the graded particle size of the tin-doped silicon oxide is Dmin≥1.5μm, D10≥3μm, 5≤D50≤7μm, Dmax≤10μm, and the value of (D90-D10) / D50 is controlled to be 0.6~1.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In the step S4, the mass ratio of the S3 product to dimethylcyclopentadienyl magnesium is (0.72-1.59): 1; And / or, the temperature of bismethylcyclopentadienylmagnesium in the gas reactor is 80° C. to 150° C.; And / or, the inert gas is one or more of helium, neon, argon, krypton, and xenon; And / or, the volume ratio of the inert gas to the dimethylcyclopentadienyl magnesium vapor is 4:1 to 1:1; And / or, the sintering process also needs to control the rotation speed of the rotary kiln, and the rotation speed of the rotary kiln is 0.25r / min~2r / min; And / or, the sintering is a two-stage sintering, the first stage sintering temperature is 300℃~500℃, the sintering time is 2h~6h, the second stage sintering temperature is 600℃~800℃, the sintering time is 2h~4h, and the heating rate of the sintering process is 1℃ / min~3℃ / min.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step S5, the median particle size D50 of molybdenum disulfide is 10 nm to 200 nm; And / or, the mass ratio of the intermediate product A to molybdenum disulfide is 99:1 to 97:3; and / or, the mass ratio of the intermediate product A to diphenyl disulfide is 99:1 to 96:4; And / or, the oxygen flow rate is 1 ml / min to 5 ml / min; And / or, the reaction temperature is 20-60°C, and the reaction time is 0.5h-3h; And / or, the secondary heating temperature is 160-300° C. and the heat preservation time is 0.5 h-2 h.

8. The silicon-based negative electrode material prepared by the method according to any one of claims 1 to 7.

9. Use of the silicon-based negative electrode material according to claim 8 in the preparation of lithium-ion batteries.

10. A lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The material of the negative electrode includes the silicon-based negative electrode material according to claim 8.

Citation Information

Patent Citations

  • Silicon oxide composite for anode material of secondary battery and method for preparing the same

    CN108630887A

  • A method for preparing a magnesium silicate-carbon coated silicon suboxide composite anode material

    CN110993900B

  • Silicon-based active material-polymer composite and preparation method therefor

    CN108140822A

  • Lithium ion battery silicon-based composite negative electrode material and preparation method thereof

    CN113506861A

  • Preparation method of magnesium-tin-doped silicon-carbon negative electrode material

    CN116169257A